The training of master’s students for teaching profession in technical higher educational institutions - Vykhrushch, Vira; Zinchuk, Iryna (Lviv Politechnic Publishing House, 2017)
The relevant problems of master’s students’ training as future teachers in the context of technical educational institutions are caused by their mental differences as to the formation of “I-concept of a personality” and “I-concept of a teacher”. The low level of empathy of master’s students of technical higher educational institutions and lack of proper motivation cause the following problems in their methodical training: lack of positive experience in communication with a teacher(teachers) at school (higher educational institution) and indifferent/ neutral/ negative attitude to pedagogic activity, unwillingness to analyse the pedagogic interaction as a developing situation from a personal life; rejection of reasonable methodical techniques which are used by a teacher; false conception about the essence of didactic interaction in higher education. The low level of affiliation and the unjustified high” over-confident emptiness”, the wrongfully high level of anticipation concerning personal estimation as a subject of training plays a negative role in a formation of a master’s student as a teacher.
Keywords: master’s students; technical higher educational institution; future teacher; didactic interaction; methodical training; empathy; affiliation; motivation of studying; “I-concept of a teacher”